2021
DOI: 10.1101/2021.03.16.435574
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single cell RNA sequencing of theStrongylocentrotus purpuratuslarva reveals the blueprint of major cell types and nervous system of a non-chordate deuterostome

Abstract: Identifying the molecular fingerprint of organismal cell types is key for understanding their function and evolution. Here, we use single cell RNA sequencing (scRNA-seq) to survey the cell types of the sea urchin early pluteus larva, representing an important developmental transition from non-feeding to feeding larva. We identified 21 distinct cell clusters, representing cells of the digestive, skeletal, immune, and nervous systems. Further subclustering of these revealed a highly detailed portrait of cell div… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 153 publications
(183 reference statements)
0
9
0
Order By: Relevance
“…It is important to stress out that previous studies from our group demonstrated that sea urchin could potentially represent an intermediate stage in pancreas evolution, since the larva contains, apart from the endodermally-derived endocrine and exocrine-like cell types (Perillo et al, 2016). Moreover we recently provided evidence that sea urchin larvae possess an additional neuronal population with a pancreatic-like gene toolkit, whose differentiation is Pdx1dependent, and was probably co-opted by modern endocrine pancreatic cells (Paganos et al, 2021). This scenario is also supported by the molecular and functional similarities of mammalian neurons and β pancreatic cells (Arntfield and van der Kooy, 2011).…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…It is important to stress out that previous studies from our group demonstrated that sea urchin could potentially represent an intermediate stage in pancreas evolution, since the larva contains, apart from the endodermally-derived endocrine and exocrine-like cell types (Perillo et al, 2016). Moreover we recently provided evidence that sea urchin larvae possess an additional neuronal population with a pancreatic-like gene toolkit, whose differentiation is Pdx1dependent, and was probably co-opted by modern endocrine pancreatic cells (Paganos et al, 2021). This scenario is also supported by the molecular and functional similarities of mammalian neurons and β pancreatic cells (Arntfield and van der Kooy, 2011).…”
Section: Introductionmentioning
confidence: 61%
“…The Single cell RNA data analyzed in this study originate from the study by Paganos et al (2021) as they have been deposited in Dryad under the unique identifier https://doi.org/ 10.5061/dryad.n5tb2rbvz. Subclustering analysis has been performed as described in Paganos et al (2021) using the Seurat scRNA-seq R package (Butler et al, 2018;Stuart et al, 2019).…”
Section: Single Cell Rna Sequencing Analysismentioning
confidence: 99%
See 3 more Smart Citations